Mesenchymal stem cell fate is regulated by the composition and mechanical properties of Collagen Glycosaminoglycan scaffolds - O'BRIEN, FERGAL (Elsevier, 2012)
In stem cell biology, focus has recently turned to the influence of the intrinsic properties of the extracellular matrix (ECM), such as structural, composition and elasticity, on stem cell differentiation. Utilising collagen-glycosaminoglycan (CG) scaffolds as an analogue of the ECM, this study set out to determine the effect of scaffold stiffness and composition on naive mesenchymal stem cell (MSC) differentiation in the absence of differentiation supplements. Dehydrothermal (DHT) and 1-ethyl-3-3-dimethyl aminopropyl carbodiimide (EDAC) crosslinking treatments were used to produce three homogenous CG scaffolds with the same composition but different stiffness values: 0.5, 1 and 1.5 kPa. In addition, the effect of scaffold composition on MSC differentiation was investigated by utilising two glycosaminoglycan (GAG) types: chondroitin sulphate (CS) and hyaluronic acid (HyA). Results demonstrated that scaffolds with the lowest stiffness (0.5 kPa) facilitated a significant up-regulation in SOX9 expression indicating that MSCs are directed towards a chondrogenic lineage in more compliant scaffolds. In contrast, the greatest level of RUNX2 expression was found in the stiffest scaffolds (1.5 kPa) indicating that MSCs are directed towards an osteogenic lineage in stiffer scaffolds. Furthermore, results demonstrated that the level of up-regulation of SOX9 was higher within the CHyA scaffolds in comparison to the CCS scaffolds indicating that hyaluronic acid further influences chondrogenic differentiation. In contrast, enhanced RUNX2 expression was observed in the CCS scaffolds in comparison to the CHyA scaffolds suggesting an osteogenic influence of chondroitin sulphate on MSC differentiation. In summary, this study demonstrates that, even in the absence of differentiation supplements, scaffold stiffness can direct the fate of MSCs, an effect that is further enhanced by the GAG type used within the CG scaffolds. These results have significant implications for the therapeutic uses of stem cells and enhance our understanding of the physical effects of the in vivo microenvironment on stem cell behaviour.
IN_PRESS
Keywords: Bioengineering; collagen-glycosaminoglycan (CG) scaffolds; stem cell biology; mesenchymal stem cell